Analisis Pelaksanaan Fungsi Pengawasan Inspektorat Daerah Kabupaten Manggarai Barat - Lusia Permatasari Yunita Oban; Melkisedek N. B. C. Neolaka; David Wilfrid Rihi; Ernestus Holivil (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the implementation of the supervisory function by the Regional Inspectorate of West Manggarai Regency based on the supervisory process stages proposed by Handoko. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. The results show that the supervisory function has been implemented in accordance with established stages, including standard setting, performance measurement, implementation, deviation analysis, and corrective actions. However, the effectiveness of supervision remains suboptimal due to limited human resources, the large number of supervisory objects, inadequate facilities, and weak follow-up on audit recommendations. In addition, the supervision system tends to be reactive rather than preventive, as indicated by recurring findings. These conditions reflect a gap between the theoretical framework and practical implementation of supervision. Therefore, strengthening auditor capacity, improving risk-based supervision systems, and enhancing commitment to follow-up actions are necessary to improve supervision effectiveness and support the realization of accountable and transparent governance.